Pengaruh Keragaman Produk Citra Merek dan Kepercayaan Konsumen terhadap Keputusan Pembelian dengan Minat Beli Sebagai Variabel Intervening di Marketplace Shopee - Neneng Hardianti; Henny Welsa; Nonik Kusuma Ningrum (J-MAS (Jurnal Manajemen dan Sains), 2023)
The emergence of the internet today changed the way people communicate. The internet continues to show its intelligence and sophistication through updates from time to time to make it easier for humans to improve their capabilities and support all activities they carry out every day. This study aims to determine the relationship between product diversity, brand image and consumer trust in purchasing decisions through purchase intentions such as the Shopee Marketplace. This study used a quantitative approach by taking 125 samples in the Sarjanawiyata Tamansiswa Yogyakarta University students. Selected by using purposive sampling technique. Questionnaire data collection methods and literature studies related to the indicators used. This study shows that product diversity has a positive and significant effect on purchase intention.